Problematika Penyalahgunaan Bantuan Sosial Guna Memperoleh Keuntungan Pribadi : Motif Dan Solusi Menurut Prespektif Ekonomi Islam (Studi Kasus Di Desa Karangtengah Kecamatan Ampelgading Kabupaten Pemalang) - Utami, Lutfi Ayu Fadhilah; Adinugraha, Hendri Hermawan (Robust: Research of Business and Economics Studies, 2024)
The government has sought welfare for underprivileged people through social assistance programs. However, there are problems in its distribution that prevent the goal of social assistance from being achieved, in fact the poverty rate increases. One of the problems with misuse of social assistance itself is the inaccuracy of targeting social assistance recipients due to a lack of updated recipient data and misuse of the social fund budget by certain individuals in taking advantage of profit opportunities. In this research, we examine the problem of misuse of social assistance in Karangtengah village, from motives to solutions according to an Islamic economic perspective. The type of research carried out is legal research with a case and statutory approach. The data collection technique uses observation and literature techniques. The results of the research show that the problem of misuse of social assistance in Karangtengha village is due to selfish and self-serving motives and also due to non-transparency of data and lack of supervision, this clearly deviates from Islamic teachings because in Islam it is forbidden to take other people's property in vain, the solution is to increase socialization so that public self-awareness is formed and supervision is tightened and there is transparency.